A contrastive analysis of Korean-Indonesian phonological structures - Asma Azizah (Journal of Korean Applied Linguistics, 2021)
This paper discusses the contrastive analysis of Korean-Indonesian phonological structure. The contrastive analysis here covers phonological correspondence and phonotactic structure between Korean and Indonesian. It also provides implications to pronunciation learning, especially Korean language learners in Indonesia. This paper is a descriptive qualitative research, using literature study from books, journals, and other related resources. This study revealed that Korean had more monophthongs and diphthongs than Indonesian, with Correspondence between Indonesian’s ‘ə’ and Korean’s ‘ɨ’, Korean’s ‘ə (ㅓ), o (ㅗ)’ and Indonesian’s ‘o’, and Korean’s ‘e (ㅔ), ɜ (ㅐ)’ and Indonesian’s ‘e’. However, Korean and Indonesian had different classification of consonant’s manner of articulation, especially on correspondence between voicing and affricative markedness. On syllable structure, Korean was considered to have stricter syllable structure than Indonesian, as seen on constraint applied on syllable.  These findings will help instructor create more effective pronunciation learning, with a comprehensive syllabus in using phonological theory and language skills. However, the suprasegmental aspect and phonological process are excluded from this research.